Úplné znenie zákona o používaní elektronickej registračnej pokladnice
Zákon č. 289/2008 Z.z. v znení zákona č. 465/2008 Z.z., zákona č. 504/2009 Z.z., zákona č. 494/2010 Z.z. a zákona č. 331/2011 Z.z.